2015
DOI: 10.1007/s10792-015-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival mucoepithelial hyperplasia of the elderly

Abstract: The ocular surface is exposed to many chronic inflammatory stimuli, and goblet cell hyperplasia of the conjunctiva occurs in many situations. We report two cases of epithelial goblet cell hyperplasia with nonspecific chronic inflammation which occurred on the internal canthus of elderly people. These cases shared the same clinicopathological features that mimicked neoplastic lesion macroscopically, but are composed of nonspecific inflammatory changes pathologically. Immunostaining of the tissue showed few IgG4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Since the ocular surface is exposed to numerous infectious and noninfectious agents or allergens, hyperplastic changes can occur due to nonspecific chronic inflammation of the conjunctiva (2). Ohashi et al (3) reported of two cases of conjunctival mucoepithelial hyperplasia amongst elderly patients. Specifically, nodular lesions found on the internal canthus were presented in both patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since the ocular surface is exposed to numerous infectious and noninfectious agents or allergens, hyperplastic changes can occur due to nonspecific chronic inflammation of the conjunctiva (2). Ohashi et al (3) reported of two cases of conjunctival mucoepithelial hyperplasia amongst elderly patients. Specifically, nodular lesions found on the internal canthus were presented in both patients.…”
Section: Introductionmentioning
confidence: 99%